Risk of low levels of blood group antibodies mediating hemolysis in ABO-incompatible neonates with negative three hemolysis tests - Hongxing Lin; Pingxiang Luo; Chen Liu; Xiaosong Lin; Chengwen Que; Wenhui Zhong (Frontiers Media S.A., 2024)
ObjectiveTo explore the risk of low-level blood group antibody-mediated hemolysis in ABO-incompatible newborns with negative three hemolysis tests, aiming to assist in the identification and management of neonatal jaundice.MethodsA retrospective case-control study was performed in 892 children with jaundice. The patients were divided into three groups: group I, ABO compatible, negative three hemolysis tests; group II, ABO incompatible, negative three hemolysis tests; and group III, ABO incompatible, positive three hemolysis tests. We analyzed the differences in clinical data, blood routine and biochemical laboratory results.Results(1) Patients in group II had higher levels of mean corpuscular volume (MCV), standard deviation of red blood cell volume distribution width (RDW-SD), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), alkaline phosphatase (ALP), and bile acid (BA) than those in group I (P < 0.05). However, there were no statistically significant differences in the MCV, ALT, ALP and BA levels between groups II and III (P > 0.05). (2) Mean corpuscular hemoglobin concentration (MCHC) >359.5 g/L, cell volume distribution width (RDW-CV) >15.95%, and reticulocyte count (RET) >4.235% were identified as independent predictors of positive hemolysis test results (P < 0.001). The combination of MCHC, RDW-CV, and RET% yielded an AUC of 0.841.ConclusionLow-level blood group antibody-mediated hemolysis may occur in ABO-incompatible neonates even when three hemolysis tests are negative. Changes in liver function parameters must be monitored. The combination of MCHC, RDW-CV, and RET% can be used to improve the detection rate of HDN.